Managing A Complex Adaptive Ecosystem: Towards A Smart Management Of Industrial Heritage Tourism - Perfetto, Maria Concetta; Vargas-Sánchez, Alfonso; Presenza, Angelo (Journal of Tourism, Sustainability and Well-being, 2016)
This paper is focused on the concept of business ecosystem, which is a relatively new field in management research. Furthermore, there is a second emerging research approach in social sciences named “complexity theory” that considers ecosystems, and business ecosystems, as complex adaptive systems. The main aim is to connect both by bringing new insights under the basis of a smart vision of tourism. In particular, we propose a theoretical discussion of the aforementioned concepts by applying them to the specific context of Industrial Heritage Management. The Industrial Heritage (i.e.: mining sites, old infrastructures, museums and historic places related to industry…) is chosen because it appears well representative: it is characterized by a complex and dynamic structure which consists of an interconnected population of stakeholders and several tangible and intangible resources to recover, organize and then manage. It follows that the management of this ecosystem should take into account many factors simultaneously. Based also on the emergent initiative of Smart Tourism, a conceptual model is presented, in which each component is explained and the focal complexity aspects appearing in this business ecosystem are highlighted. We conclude with a set of propositions for recommending new paths for future studies.